An Analysis of Reforms and Trends in The National Healthcare System of North Macedonia During the Transition Period - Ollogu, Elisabeta Bajrami; Pavlovski, Daniel; Shaipi, Urime Demiri (European Journal of Social Science Education and Research, 2024)
This research provides an analysis of the healthcare system in North Macedonia aiming to address the results of reforms, current functioning of the system and analyze the trends whilst reforming some segments of the system with particular focus in the last two decades. HealthCare System, since the country’s independence has been subject of many reforms that have brought various changes in terms of organization and governance and most importantly, in the delivery of health services and accessibility for the citizens. There is a dominance of public healthcare services and institutions but private institutions have quietly increased in the last two decades. One relevant and most emerging problems of current healthcare system may refer to a lack of accessibility of healthcare services for all citizens, which automatically leads to the social exclusion problem for some categories (i.e. Roma community; rural population, etc.). From a methodological aspect, the research makes use of different public policy documents by focusing in the following phases of healthcare system development: post socialist (1991-1998), pro-market (1998-2006) and manifesto-driven (2006-nowadays). In addition, it provides empirical evidence in the form of a survey conducted with various interest groups nationwide assessing their ideological preferences regarding the healthcare system: functioning, financing, etc. The findings of this study show that regardless many improvements that the reforms have produced, still the country’s healthcare system remains qualitatively far away compared to European countries. According to the perceptions of interest groups seems that there is a tendency of increased commercialization of health services nationwide, which from a socio-economic aspect, leads to potential social exclusion for some categories in terms of access to qualitative services.
Keywords: healthcare, North Macedonia, reforms, services, marketization